Geographical proximity and technological intensity in manufacturing: evidence from the periphery of the São Paulo-Brasília axis at the beginning of the 21st century | Proximidade geográfica e intensidade tecnológica na indústria: evidências da periferia do eixo São Paulo-Brasília no início do século XXI - Mesquita, Fernando Campos; Sampaio, Daniel Pereira (Revista Brasileira de Estudos Urbanos e Regionais, 2017)
This article analyzes manufacturing dynamics along the periphery of the São Paulo-Brasília axis from a perspective that studies the extent to which technological intensity has been influenced by being distant from the core. The aim is to investigate geographical proximity as a limiting factor in the ongoing process of manufacturing deconcentration in Brazil. To measure this phenomenon, the São Paulo-Brasília axis was divided into three peripheral regions: nearby, middle and distant. Subsequently, data related to the industrial workforce, the level of average real salaries, and qualifications of the workforce were used to analyze each of the subdivisions during 2002, 2008, 2014. Results demonstrate that even within a context of investments in transport infrastructure and new possibilities created by advances in communication technologies, the heterogeneities of manufacturing became more intense. The regions geographically closer to the Metropolitan Region of São Paulo demonstrate a higher technological qualification of its industrial structure, while those furthest away are primarily composed of labor-intensive natural resource industries.